2000
DOI: 10.1016/s0014-5793(00)01192-3
|View full text |Cite
|
Sign up to set email alerts
|

The gene encoding DRAP (BACE2), a glycosylated transmembrane protein of the aspartic protease family, maps to the Down critical region

Abstract: We applied cDNA selection methods to a genomic clone (YAC 761B5) from chromosome 21 located in the so-called Down critical region' in 21q22.3. Starting from human fetal heart and brain mRNAs we obtained and sequenced several cDNA clones. One of these clones (Down region aspartic protease (DRAP), named also BACE2 according to the gene nomenclature) revealed a striking nucleotide and amino acid sequence identity with several motifs present in members of the aspartic protease family. In particular the amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
94
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 31 publications
2
94
0
1
Order By: Relevance
“…Increased beta-secretase activity in DS with age may reflect BACE1 activity [64], but also possibly BACE2, which has approximately a 64% amino acid similarity to BACE1 [1] and is present on chromosome 21 in the DS obligate region [1]. Developmentally, BACE2 protein levels are significantly higher in DS fetal tissue relative to controls [2].…”
Section: Discussionmentioning
confidence: 98%
“…Increased beta-secretase activity in DS with age may reflect BACE1 activity [64], but also possibly BACE2, which has approximately a 64% amino acid similarity to BACE1 [1] and is present on chromosome 21 in the DS obligate region [1]. Developmentally, BACE2 protein levels are significantly higher in DS fetal tissue relative to controls [2].…”
Section: Discussionmentioning
confidence: 98%
“…BACE1 and BACE2 are two highly homologous membranebound aspartyl proteases that can process APP at the ␤-secretase site (1)(2)(3)(4)(5)(6)(7)(8). Although both enzymes exhibit many of the characteristics expected for ␤-secretase, it has been quite convincingly demonstrated that BACE1 is in fact the major ␤-secretase responsible for A␤ generation in brain (9 -11).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…BACE1 knock-out mice completely lack A␤ production in the brain (14,15), indicating that BACE1 carries majority of ␤-secretase activity in the brain. BACE2 may be important in Down syndrome pathology, because the enzyme is encoded by chromosome 21 (12) and its expression is elevated in trisomic brains (16).…”
Section: A Characteristic Feature Of Alzheimer Disease (Ad)mentioning
confidence: 99%